2016
DOI: 10.3389/fpls.2016.01521
|View full text |Cite
|
Sign up to set email alerts
|

Coconut Lethal Yellowing Diseases: A Phytoplasma Threat to Palms of Global Economic and Social Significance

Abstract: The recent discovery of Bogia coconut syndrome in Papua New Guinea (PNG) is the first report of a lethal yellowing disease (LYD) in Oceania. Numerous outbreaks of LYDs of coconut have been recorded in the Caribbean and Africa since the late Nineteenth century and have caused the death of millions of palms across several continents during the Twentieth century. Despite the severity of economic losses, it was only in the 1970s that the causes of LYDs were identified as phytoplasmas, a group of insect-transmitted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
71
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(72 citation statements)
references
References 177 publications
(295 reference statements)
0
71
0
1
Order By: Relevance
“…This indicates that the collection of Hemiptera species (even those present in large numbers) from host plants that are proven to be infected by phytoplasmas (two diverse strains) is not evidence for vector status. Clearly sampling over a larger spatio-temporal scale will be necessary to establish which insect species may test PCR positive though transmission tests are necessary to provide definitive evidence of vector capacity32.…”
Section: Discussionmentioning
confidence: 99%
“…This indicates that the collection of Hemiptera species (even those present in large numbers) from host plants that are proven to be infected by phytoplasmas (two diverse strains) is not evidence for vector status. Clearly sampling over a larger spatio-temporal scale will be necessary to establish which insect species may test PCR positive though transmission tests are necessary to provide definitive evidence of vector capacity32.…”
Section: Discussionmentioning
confidence: 99%
“…Lethal palm declines also occur in some countries of North and Central America, Africa, Caribbean and Oceania (Dollet et al ., ; Harrison et al ., ; Gurr et al ., ). They are quarantine diseases that still remain undetected in Brazil.…”
Section: Introductionmentioning
confidence: 97%
“…Mycoplasmas are now referred as phytoplasmas, i.e., prokaryotes lacking cell walls, infecting a wide range of plant taxa (Marcone 2015). Plant diseases caused by, or associated with, phytoplasmas occur in many agricultural and horticultural plants species of importance (Bertaccini et al 2014;Arunkumar et al 2016;Gurr et al 2016). There are several reviews on various aspects of phytoplasma research (Marcone 2011;Kube et al 2012;Marcone 2012;Bertaccini et al 2014;Bertaccini 2015;Marcone 2015;Gurr et al 2016;Trivedi et al 2016).…”
Section: Discovery Of the Pathogenmentioning
confidence: 99%
“…PCR-based methods revealed that Ca. Phytoplasma cynodontis belongs to 16SrI, which is one of the major groups of phytoplasmas associated with different plant species reported to be infected with phytoplasmas worldwide (Lee et al 1998;Hogenhout et al 2008;Bertaccini, Duduk 2009;Laimer et al 2009;Marcone 2011;Rao et al 2011;Delić 2012;Kube et al 2012;Gurr et al 2016). An understanding of phytoplasma ecology and epidemiology has increased as a result of the use of these PCR-based methods (Martin et al 2000).…”
Section: Detectionmentioning
confidence: 99%
See 1 more Smart Citation